Bomber boys the Ruhr, the Dambusters and bloody Berlin - Wilson, Kevin, 1942- (Cassell military paperbacks, 2006)
A gripping account of the everyday heroism of British bomber crews in 1943 - the year when Bomber Command believed it could win WWII by bombing alone.